2014
DOI: 10.1038/ejhg.2013.296
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of genetics and genetic testing and information needs and preferences of adults with inherited retinal disease

Abstract: Advances in sequencing technology and the movement of genetic testing into all areas of medicine will increase opportunities for molecular confirmation of a clinical diagnosis. For health-care professionals without formal genetics training, there is a need to know what patients understand about genetics and genetic testing and their information needs and preferences for the disclosure of genetic testing results. These topics were explored during face-to-face interviews with 50 adults with inherited retinal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…At the same time, participants showed their willingness to receive more information about the implications, both in terms of inheritance pattern and prognosis of their condition to make informed choices. It is therefore pivotal that individuals have access to genetic counselling services, where they can receive accurate, balanced and unbiased information and support to make informed reproductive decisions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, participants showed their willingness to receive more information about the implications, both in terms of inheritance pattern and prognosis of their condition to make informed choices. It is therefore pivotal that individuals have access to genetic counselling services, where they can receive accurate, balanced and unbiased information and support to make informed reproductive decisions …”
Section: Discussionmentioning
confidence: 99%
“…The following characteristics were included in the sampling frame: age (across four groups considered to represent different life stages: 16–25 years, 26–39 years, 40–59 years and 60+ years), gender, ethnicity, education, severity of visual impairment, parenting status, and family history of IRD. Both the telephone questionnaire and the format for the subsequent interviews have been described in detail previously …”
Section: Methodsmentioning
confidence: 99%
“…Recent work from our group has demonstrated that the information needs of many patients with inherited retinal disease appear to be unmet. 17 Our study presents a number of limitations of the experimental nature of CV surveys. 18,19 Typically, the reported willingness to take the test and to pay for testing in this study is only a proxy for actual uptake of testing and true willingness to pay.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effect of misleading wording becomes particularly apparent in the findings of patients' genetic misconception (McKibbin et al, 2014;Pentz et al, 2012). This phenomenon is likely to be essential for any molecular cancer research when physicians refer to genetics, gene banks, genetic testing or tumour genetics (Beskow, Dombeck, Thompson, Watson-Ormond, & Weinfurt, 2015;Gray et al, 2012 General wording such as "optimisation" or "personalisation" tend to undermine (rather than facilitate) the correct understanding of this important research aim.…”
Section: Mr 18 B 1 St Interview: Personalised Medicine? […] Notmentioning
confidence: 99%